Development of grating for the optical addressing of Sr+ ions with data analysis techniques - Lim, Yu Dian (2023)
In this study, SiN-based gratings with various radius of curvature (r) are designed and fabricated for the optical addressing of trapped Sr+ ion. The beam width of the light coupled out from the gratings is investigated using a self-developed Python-based data analysis technique. It is found that the r values have insignificant influence on the beam width along x-axis; whereas the beam waist along y-axis reduces from 13.96 to 12.3 µm as r increases from 15 to 20 µm, then increases gradually to 20.51 µm as the r value further increases to 60 µm. The obtained results can provide a versatile solution on the optical addressing of trapped Sr+ for applications in quantum engineering.